A self-assembly nano-prodrug for triple-negative breast cancer combined treatment by ferroptosis therapy and chemotherapy. (15th March 2023) - Chen, Yuan; Yao, Zhuo; Liu, Peilian; Hu, Qida; Huang, Yong; Ping, Li; Zhang, Fu; Tang, Honglin; Wan, Tao; Ping, Yuan; Li, Bowen
Abstract: Chemotherapeutics have been recommended as the standard protocol for inoperable patients with triple-negative breast cancer (TNBC) at advanced stage, yet limited success has been achieved in prolonging survival rates by this monotherapy. A major reason for this failure is the chemo-resistance from traditional apoptotic pathways resulting in poor therapeutic effect. Ferroptosis has become a powerful modality of no-apoptotic cell death, which can effectively evade chemo-resistance in apoptotic pathways. Herein, we propose an active-targeting small-molecular self-assembly nano-prodrug for co-delivery of chemotherapeutics (CPT), Ferrocene (Fc) and GPX4 inhibitor (RSL3) to overcome the chemo-resistance from traditional apoptotic pathways. In this nano-prodrug, the disulfide linkage not only serves as a GSH-responsive trigger, but also exhibits a stable self-assembly behavior that forms nanoparticle. Interestingly, the RSL3 can be loaded during this self-assembly process that forms a three-components nano-prodrug. In tumor environment, the high GSH level can disassemble the nano-prodrug to trigger the release of the parent drug, which can improve the therapeutic effect by synergistic effects of ferroptosis and apoptosis. In different TNBC mice models, the nano-prodrug is encapsulated into RGD-modified phospholipid micelles (DSPE-PEG2000-RGD) and exhibits high anti-tumor and anti-metastasis efficacy, especially in orthotopic models. The application of ferroptosis to assist the enhancement of chemotherapeutics may serve as a promising strategy for TNBC treatment. Statement of significance: Chemotherapeutics have been recommended as the standard of care for palliative and adjuvant treatment in patients with triple-negative breast cancer (TNBC), yet limited success has been achieved in prolonging the overall survival of patients by this monotherapy. A major reason for this failure is the chemo-resistance from traditional apoptotic pathways resulting in poor therapeutic effect. Thus, the co-delivery of the apoptosis and ferroptosis drug may overcome or evade the resistance in chemotherapy-induced apoptotic pathways and provide a promising strategy to combat TNBC. In this work, we developed a small-molecular self-assembly nano-prodrug for co-delivery of chemotherapeutics (CPT), Ferrocene (Fc) and ferroptosis resistance inhibitor (RSL3), which could overcome the chemo-resistance and improve the therapeutic effect by synergistic effects of ferroptosis and apoptosis. Graphical abstract: Image, graphical abstract